2022
DOI: 10.3390/ani12202811
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Continuous and Intermittent Use of Bovine Colostrum on Laying Japanese Quails: Egg Performance and Traits, Blood Biochemical and Antioxidant Status

Abstract: The Japanese quail (Coturnix japonica) is farmed for its eggs and meat across the globe. A series of experiments were conducted to evaluate the effect of the permanent or intermittent use of different levels of BC (bovine colostrum) on the egg performance and traits, carcass characteristics, blood biochemical and antioxidant status of laying Japanese quails. In this study, 200 laying quails were used for a duration of six weeks (week 24 to 30) to measure the selected parameters. Treatments included: (1) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mokhtarzadeh et al [31] found a significant increase (p < 0.01) in SOD serum concentrations in Japanese quails supplemented with BC (2% and 4%) for six weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Mokhtarzadeh et al [31] found a significant increase (p < 0.01) in SOD serum concentrations in Japanese quails supplemented with BC (2% and 4%) for six weeks.…”
Section: Discussionmentioning
confidence: 97%
“…In order to measure the triglyceride and cholesterol levels of blood samples, first the samples were separated in Pars azmoon commercial diagnostic kits, and then they were measured by colorimetric and photometric enzymatic methods, as suggested by Baghban-Kanani et al [ 37 ], Nobakht et al [ 38 ] and Feshanghchi et al [ 39 ]. Glucose was measured using a hexokinase enzyme method according to the proposed methods by Kunst [ 40 ], Hosseintabar et al [ 41 ], Li et al [ 42 ] and Mokhtarzadeh [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the positive effects of continuous and intermittent use of cow’s colostrum and determining the consumption of the minimum level of cow’s colostrum in the feeding of laying Japanese quails have been obtained [ 38 ], but so far, no research has been conducted on the evaluation of the effects of cow’s colostrum (a natural additive) and probiotics (an artificial additive) in laying Japanese quails. Therefore, the aim of this research is to evaluate the effects of different levels of cow’s colostrum, with and without probiotics, on performance, egg quality, carcass traits, blood parameters, and antioxidant status in Japanese quails.…”
Section: Introductionmentioning
confidence: 99%